ON THE ANCIENT RELATIONS BETWEEN THE TURKIC AND KOREAN PEOPLES - Gaybullah BABAYAR (Türk Uygarlığı Araştırma ve Uygulama Merkezi Dergisi, 2023)
In early periods there lived mainly Turkic, Mongol, Tungus, Manchu and Korean tribes in the northern and northeastern parts of the Asian Continent and they were neighbors to each other. According to linguistic studies of some researchers, those tribes in the origin were belonged to one linguistic family, i.e. to Altai Language Family and during the historical process they separated into several modern languages. However, today the relativity of Turkic, Mongol, Tungus and Manchu languages have been clarified thoroughly, and all of these language groups are accepted as “Altai language family” by world known linguists, the problem of dependency of the Korean to these group hasn’t been solved yet.